Process Formulation and Evaluation of Jamun Flavored Functional Yoghurt Drink Prepared from Kodo Millet - Bhatt, Meenakshi; hooda, ankita; Dutt Tripathi, Abhishek; Rai, Himanshu Kumar; Sen, Munmun; singh, sulaxana (Indian Journal of Dairy Science, 2026)
Millets are being termed as nutri-cereals because of their inherent therapeutic properties that have been associated with increased benefits to the health of an individual. Some minor millets have great functional properties and are yet to be explored. One amongst these is Kodo millet which has anti-diabetic and antioxidant properties that exert their potency in reducing the risk of CVD, oxidative stress, certain cancers, and obesity. Jamun, a fruit that has been in use since time immemorial bestows similar properties. Therefore, the study was aimed at preparing a functional yoghurt drink from these two ingredients thereby complementing and enhancing the functional properties. The Kodo millet was given treatments of soaking and germination. The results for the yoghurt were determined for their physiochemical properties, antioxidant properties, and sensory characteristics. As per the results, the nutritional profile involving protein (9.9%), fat (3.17 %), crude fiber (6.16%), and ash percentage (3.17%), of the yoghurt drink was superior when made from germinated Kodo millet. The physio-chemical properties such as pH (4.50), TSS (14.87oBrix), and acidity (0.155%) of the germinated Kodo millet yoghurt drink were slightly different from the other two samples except for viscosity which was significantly higher in untreated millet yoghurt (180.77 cP). The germinated Kodo millet drinkable yoghurt had the highest antioxidant activity (60.31%) while the untreated Kodo grain yoghurt had the highest total phenolic content (9.05 mg GAE/ml) followed by germinated grain yoghurt (7.83 mg GAE/ml). In terms of sensory attributes, the yoghurt beverage prepared from germinated Kodo millet obtained the maximum sensory score. The present study has the potential for commercialization in the market as the prepared yoghurt beverage offers certain health benefits and can cater to a wider section of our society, from the elderly to toddlers.